KONSTRUKSI DAKWAH NOMADEN NYAI NIKMAH DI KABUPATEN LUMAJANG - Robith Abdillah Al-hadi (Indonesian Journal of Islamic Communication, 2020)
Da'wah is an important thing to do as an effort to invite the ummah to the good way. By the kinds of methods which is used by the da'i, it makes mad'u easily accept the da'wah process. As the figure of Nyai Nikmah in Lumajang, who has its own uniqueness in dakwah, that is dakwah in a nomadic way. The focus of this study is about how the construction of the nomadic da'wah of Nyai Nikmah in Lumajang. The purpose and benefit of this study is to find out and make a reference about the varieties of da'wah, especially in terms of nomadic dakwah. As well as reveal in depth how the nomadic dakwah. This study is phenomenological qualitative in which the author explores the new topics, describes social phenomena and explains how the social phenomena occur, which in this case are nomadic dakwah. this study uses Berger's social construction theory and da'wah theory. The results of this study indicates that the construction of Nyai Nikmah's nomadic dakwah includes three processes. The first process is externalization in which Nyai Nikmah in this case adapts to religious teachings in the form of da'wah through what her husband, Gus Nashih, ordered to dakwah. The second process is objectivation in which Nyai Nikmah has adapted the religious teachings in several areas. Nyai Nikmah increasingly established herself to dakwah nomadically. And the last process is Internalization, where the two previous processes provide the understanding and awareness to Nyai Nikmah that by nomadic dakwah, eventually Nyai Nikmah felt successful in her dakwah.